What length of after-school Learning time best promotes the development of non-cognitive ability in adolescents? Evidence from China - Sun, Huimin; Xue, Haiping (Frontiers in Psychology, 2025)
We utilized a nationally representative dataset from the China Education Panel Survey (CEPS) and applied hierarchical linear models and quadratic models to analyze the impact of after-school Learning time on adolescents’ non-cognitive ability development, aiming to identify the optimal duration. Our results show that, first, the relationship between school homework duration and the development of openness, conscientiousness, extraversion, and agreeableness follows an inverted “U” curve, while its impact on neuroticism follows a “U” curve. Considering the five dimensions of non-cognitive ability development, the optimal daily school homework duration is recommended to be no more than 39.33 min. Second, the duration of extracurricular academic tutoring exhibits an inverted “U” relationship with openness, conscientiousness, extraversion, and agreeableness, with no significant effect on neuroticism. The optimal daily duration for extracurricular academic tutoring, based on four non-cognitive ability development dimensions, is recommended to be no more than 79.83 min. Third, the effect of after-school Learning time on the development of non-cognitive abilities varies based on the socioeconomic status (SES) of the family. Adolescents from low SES families tend to benefit from longer optimal durations of school homework and extracurricular academic tutoring compared to their peers from medium and high SES families.